Characteristic point algorithm in laser ektacytometry of red blood cells. (January 2018) - Nikitin, S.Yu.; Ustinov, V.D.
Abstract: We consider the problem of measuring red blood cell deformability by laser diffractometry in shear flow (ektacytometry). A new equation is derived that relates the parameters of the diffraction pattern to the width of the erythrocyte deformability distribution. The numerical simulation method shows that this equation provides a higher accuracy of measurements in comparison with the analogous equation obtained by us earlier.